Ethnic Disparities in the Transition to Home Ownership - Aslan Zorlu; Clara H. Mulder; Ruben van Gaalen (Institute for the Study of Labor (IZA), 2014)
This paper examines ethnic disparities in the transition to home ownership using longitudinal register data from the Netherlands. The study performs a discrete duration model to account for individual and parental background and neighbourhood conditions. Subsequently, the size of explained variance in the home ownership gap between Dutch and ethnic minority groups is estimated using the Oaxaca-Fairlie non-linear decomposition method. The analysis indicates that the home ownership gap is the highest for Moroccans (0.07) of which only 0.042 is explained by the observed characteristics. For Turkish residents, 0.043 of the total 0.046 gap is explained by their background characteristics. The estimated transition rate to home ownership for Surinamese migrants would have been slightly higher than for Dutch residents if they had the same characteristics as Dutch residents. Western migrants have the smallest gap (0.024), of which 0.021 is explained by their observed characteristics.
Keywords: R21; 330; immigrants; housing tenure; discrete time duration; non-linear decomposition